Marketing Strategies of Independent Musicians on Tiktok to Introduce Their Works and Enhance Personal Branding - R. Suryanti Ismail; Marissa Silooy (Jurnal Manajemen dan Profesional, 2026)
TikTok provides broad opportunities for independent musicians to promote their songs and strengthen their personal branding without the support of major record labels. This study aims to analyze the role of marketing strategies on TikTok in providing positive impacts for these musicians. Using a qualitative approach with a case study method, data were collected through observation of relevant TikTok accounts and online interviews with independent musicians who actively use the platform. The results indicate that independent musicians utilize various creative strategies to expand their audience reach, including collaborating with other content creators, producing visually engaging videos with high-quality audio, and consistently uploading content that aligns with TikTok's algorithm dynamics. In conclusion, these strategies effectively enhance audience engagement and support the development of independent musicians' public image, confirming TikTok's positive role as a viable marketing platform outside the major label system.